Nitrosation‐Dependent Caveolin 1 Phosphorylation, Ubiquitination, and Degradation and its Association with Idiopathic Pulmonary Arterial Hypertension. (1st December 2013) - Bakhshi, Farnaz R.; Mao, Mao; Shajahan, Ayesha N.; Piegeler, Tobias; Chen, Zhenlong; Chernaya, Olga; Sharma, Tiffany; Elliott, W. Mark; Szulcek, Robert; Bogaard, Harm Jan; Comhair, Suzy; Erzurum, Serpil; et al.
Abstract : In the present study, we tested the hypothesis that chronic inflammation and oxidative/nitrosative stress induce caveolin 1 (Cav‐1) degradation, providing an underlying mechanism of endothelial cell activation/dysfunction and pulmonary vascular remodeling in patients with idiopathic pulmonary arterial hypertension (IPAH). We observed reduced Cav‐1 protein despite increased Cav‐1 messenger RNA expression and also endothelial nitric oxide synthase (eNOS) hyperphosphorylation in human pulmonary artery endothelial cells (PAECs) from patients with IPAH. In control human lung endothelial cell cultures, tumor necrosis factor α–induced nitric oxide (NO) production and S‐nitrosation (SNO) of Cav‐1 Cys‐156 were associated with Src displacement and activation, Cav‐1 Tyr‐14 phosphorylation, and destabilization of Cav‐1 oligomers within 5 minutes that could be blocked by eNOS or Src inhibition. Prolonged stimulation (72 hours) with NO donor DETANONOate reduced oligomerized and total Cav‐1 levels by 40%–80%, similar to that observed in IPAH patient–derived PAECs. NO donor stimulation of endothelial cells for >72 hours, which was associated with sustained Src activation and Cav‐1 phosphorylation, ubiquitination, and degradation, was blocked by NOS inhibitor L‐NAME, Src inhibitor PP2, and proteosomal inhibitor MG132. Thus, chronic inflammation, sustained eNOS and Src signaling, and Cav‐1 degradation may be important causal factors in the development of IPAH by promoting PAEC dysfunction/activation via sustained oxidative/nitrosative stress.